Lung Ultrasound in Critical Care and Emergency Medicine: Clinical Review - Eduardo Rocca; Christian Zanza; Yaroslava Longhitano; Fabio Piccolella; Tatsiana Romenskaya; Fabrizio Racca; Gabriele Savioli; Angela Saviano; Andrea Piccioni; Silvia Mongodi (Advances in Respiratory Medicine, 2023)
Lung ultrasound has become a part of the daily examination of physicians working in intensive, sub-intensive, and general medical wards. The easy access to hand-held ultrasound machines in wards where they were not available in the past facilitated the widespread use of ultrasound, both for clinical examination and as a guide to procedures; among point-of-care ultrasound techniques, the lung ultrasound saw the greatest spread in the last decade. The COVID-19 pandemic has given a boost to the use of ultrasound since it allows to obtain a wide range of clinical information with a bedside, not harmful, repeatable examination that is reliable. This led to the remarkable growth of publications on lung ultrasounds. The first part of this narrative review aims to discuss basic aspects of lung ultrasounds, from the machine setting, probe choice, and standard examination to signs and semiotics for qualitative and quantitative lung ultrasound interpretation. The second part focuses on how to use lung ultrasound to answer specific clinical questions in critical care units and in emergency departments.